(untitled) (Journal of Pharma Insights and Research, 2024)
The Covishield vaccine, developed by a partnership between AstraZeneca and the University of Oxford, has proven invaluable in the global fight against the COVID-19 pandemic. The documented effectiveness of this product in reducing severe disease and hospitalizations has made a significant contribution to public health efforts. There have been growing concerns surrounding vaccine-induced immune thrombotic thrombocytopenia (VITT), a rare yet significant adverse event linked to Covishield and other adenoviral vector vaccines. This article offers a thorough examination of Covishield’s development process, the obstacles encountered during clinical trials, and its significance in worldwide vaccination efforts. We discussed the different incidence rates observed among various populations and age groups. The pathogenesis of VITT, which involves the production of antibodies that target platelet factor 4 (PF4), will help in understanding the mechanisms behind this uncommon condition. The article highlights the clinical manifestations of VITT, such as thrombosis and thrombocytopenia, underscoring the significance of timely recognition and medical intervention. The controversies surrounding Covishield, specifically regarding the reported cases of VITT, have been addressed. Ongoing research efforts are being made to gain a better understanding of these risks and find ways to mitigate them